2020
DOI: 10.1172/jci.insight.140532
|View full text |Cite
|
Sign up to set email alerts
|

Tirzepatide is an imbalanced and biased dual GIP and GLP-1 receptor agonist

Abstract: Tirzepatide (LY3298176) is a dual GIP and GLP-1 receptor agonist under development for the treatment of type 2 diabetes mellitus (T2DM), obesity, and nonalcoholic steatohepatitis. Early phase trials in T2DM indicate that tirzepatide improves clinical outcomes beyond those achieved by a selective GLP-1 receptor agonist. Therefore, we hypothesized that the integrated potency and signaling properties of tirzepatide provide a unique pharmacological profile tailored for improving broad metabolic control. Here, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
192
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 238 publications
(238 citation statements)
references
References 63 publications
7
192
0
4
Order By: Relevance
“…Although GLP-1R agonists developed specifically to G protein–directed signaling are yet to be tested in humans, the potential utility of this approach is supported by the recent observation that Tirzepatide, a dual GLP-1R/GIPR agonist peptide currently in late-stage clinical trials ( 18 ), and its nonacylated precursor show a significant degree of bias at the GLP-1R in favor of cAMP over β-arrestin recruitment ( 19 , 73 ). Conflicting reports exist for bias between cAMP and β-arrestin recruitment to the GIPR for Tirzepatide, with one study showing bias in favor of cAMP and another showing no difference ( 19 , 74 ). Biased agonism at the GCGR is relatively unexplored, except for a recent study of a series of dual GLP-1R/GCGR agonists in which a small response amplitude for β-arrestin-2 recruitment to GCGR hampered bias assessments ( 75 ), but should be further explored in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although GLP-1R agonists developed specifically to G protein–directed signaling are yet to be tested in humans, the potential utility of this approach is supported by the recent observation that Tirzepatide, a dual GLP-1R/GIPR agonist peptide currently in late-stage clinical trials ( 18 ), and its nonacylated precursor show a significant degree of bias at the GLP-1R in favor of cAMP over β-arrestin recruitment ( 19 , 73 ). Conflicting reports exist for bias between cAMP and β-arrestin recruitment to the GIPR for Tirzepatide, with one study showing bias in favor of cAMP and another showing no difference ( 19 , 74 ). Biased agonism at the GCGR is relatively unexplored, except for a recent study of a series of dual GLP-1R/GCGR agonists in which a small response amplitude for β-arrestin-2 recruitment to GCGR hampered bias assessments ( 75 ), but should be further explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, G protein-biased GLP-1R agonists derived from exendin-4 lead to increases in sustained insulin secretion through avoidance of GLP-1R desensitization, reduction of GLP-1R endocytosis, and resultant attenuation of GLP-1R downregulation over pharmacologically relevant time periods ( 16 , 17 ). Moreover, a GLP-1R/GIPR dual agonist (Tirzepatide) with promising results for the treatment of T2D in clinical trials ( 18 ) has recently been reported to show pronounced G protein bias at the GLP-1R, although not at the GIPR ( 19 ). In view of the current drive to develop incretin analogs jointly targeting GLP-1R, GCGR, and GIPR ( 1 ), we sought to establish whether biased agonism could similarly be achieved at the latter two receptors and to determine if this is associated with prolonged signaling responses, as seen with the GLP-1R.…”
mentioning
confidence: 99%
“…The clinical phase III data, communicated in a press release in December 2020, indicated that 51.7% of the participants can reach normal HbA1c levels with the highest dose of tirzepatide [ 98 ]. Tirzepatide was engineered from the native GIP sequence [ 95 ] and has a five-fold higher affinity to GIP-R than GLP-1R [ 99 ]. A recent publication has suggested that tirzepatide activates GIP and GLP-1 receptors differently.…”
Section: Diabetesmentioning
confidence: 99%
“…By investigating the downstream signaling molecules, the authors show that tirzepatide resembles GIP at GIP-R but has a biased agonism against GLP-1R in favor of cAMP generation over β-arrestin recruitment. In fact, the observed pharmacology of tirzepatide, such as enhanced insulin secretion, was linked to its imbalanced activity against GIP-R and biased activity towards GLP-1R [ 99 ]. Tirzepatide is associated with fewer gastrointestinal adverse effects that are commonly occurring during GLP-1R agonism but has never been reported with GIP-R activity [ 100 ].…”
Section: Diabetesmentioning
confidence: 99%
See 1 more Smart Citation